Evaluation of the Mortgage Market in Poland during the Crisis Period of 2008–2009 - Leszek Borowiec (Contemporary Economics)
The global financial crisis was a very big challenge especially for banking sector. We can say that the young Polish financial sector managed with satisfaction this challenge without many problems which troubled banking environment elsewhere in Europe. Article says that in 2009, the real estate financing market has passed credibility test during the economic slowdown. Even though banks share credit fell to the level from 2006, in whole 2009 consistently were increased sales housing loans banks. Introduced many restrictions on access to credit (increased profit margins, higher requirements for obtaining credits, additional security). Throughout 2009 banks gradually were rebuilding the level of lending, which resulted from well known government program „Family strike out on theirs own” which could have been found in banks offers.